Using Electoral Cycles in Police Hiring to Estimate the Effect of Police on Crime: Comment - McCrary, Justin (American Economic Review, 2002)
Using Electoral Cycles in Police Hiring to Estimate the Effect of Police on Crime: Comment by Justin McCrary. Published in volume 92, issue 4, pages 1236-1243 of American Economic Review, September 2002